PENGEMBANGAN PROGRAM PENINGKATAN KOMPETENSI GURU DALAM MENYUSUN PROGRAM PEMBELAJARAN INDIVIDUAL DI SLB ADITYA GRAHITA KOTA BANDUNG - Rahmawati, Kartika Nurlaila (2015)
Salah satukompetensi yang harusdimilikioleh guru profesionaladalahkompetensidalammenyusun program pembelajaran.Untuk guru pendidikankhusus, salahsatukompetensi yang harusdimilikiadalahpenyusunan Program Pembelajaran Individual yang menjadiacuandalammelaksanakanpembelajaranbagisiswaberkebutuhankhususagar hasilnyasesuaidenganstandar yang diharapkan.Kenyataan di lapanganmenunjukkanbahwaketerampilan-keterampilandalammenyusundanmengembangkan program pembelajaran individual yang terkaiteratdenganketerampilan di dalammelakukanasesmen, justruhal-halitulah yang menjadikesulitanpara guru-guru di SekolahLuarBiasa.Berdasarkanlatarbelakangpermasalahan yang ada, penelitiinginmengadakansuatuupayakonkrituntukmembantu guru agar lebihbisameningkatkankompetensinyadalammenyusun Program Pembelajaran Individual, sehinggapenelitimelakukanpenelitiandenganmengembangkansuatu program untukmeningkatkankompetensi guru tersebut.Penelitianinidilakukansecarakualitatifdenganmelaluitigalangkahprosedurpenelitian.Langkahpenelitianpertamaadalahmenggalikondisiobjektifkompetensi guru dalammemahami program pembelajaran individual.Langkah penelitian kedua merumuskan program untuk membantu meningkatkan kompetensi guru dalam menyusun Program Pembelajaran Individual. Dan langkahketigaadalahimplementasi program tersebutkepada guru. One of the competencies that must be possessed by a professional teacher is the competence in formulating the learning program.For a special education teacher, one of the competencies required is the preparation of Individual Learning Program.Individual Learning Program became the reference to conductlearning for special needs students in order to make the results based on the expected standards.But the reality in the field showed that the skills in formulating and developing the Individual Learning Program that were closely related with the skill in conducting the assessment, became the things which made difficult for teachers in special school.Based on the background of the existing problems, researchers want to organize a concerted effort to help teachers so that more can improve their competence in formulating Individual Learning Program so the researchers conducted the research by developing a program to improve the competency of teachers. This research was conducted qualitatively through three-step procedure research. The first step was exploring the objective conditions of the teacher competence in understanding Individual Learning Program. The second step was formulating a course to help improve the competency of teachers in preparing the Individual Learning Program. And the third step was the implementation of the program to the teacher.